2009
DOI: 10.1021/la902888y
|View full text |Cite
|
Sign up to set email alerts
|

XPS and ToF-SIMS Investigation of α-Helical and β-Strand Peptide Adsorption onto SAMs

Abstract: 14-mer α-helix and a 15-mer β-strand oligopeptides composed of leucine (L) and lysine (K) were used to investigate peptide adsorption and orientation onto well-defined methyl and carboxylic acid terminated self-assembled monolayer (SAM) surfaces with X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). XPS showed both peptides reached monolayer thickness on both SAMs, but significantly higher solution concentrations were required to reach this coverage on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 66 publications
7
79
0
Order By: Relevance
“…These results match the solution structure results for that FF (Fig. 4a, d), and most closely match experimental findings [9][10][11]50]. As in the case of the LKb7 peptides, it appears that the methyl-group parameters in CHARMM22 FF permit strong binding of the peptide with minimal disruption of the peptide's internal structure.…”
Section: The Lka14 Peptide Adsorbed To the Ch 3 -Samsupporting
confidence: 86%
See 3 more Smart Citations
“…These results match the solution structure results for that FF (Fig. 4a, d), and most closely match experimental findings [9][10][11]50]. As in the case of the LKb7 peptides, it appears that the methyl-group parameters in CHARMM22 FF permit strong binding of the peptide with minimal disruption of the peptide's internal structure.…”
Section: The Lka14 Peptide Adsorbed To the Ch 3 -Samsupporting
confidence: 86%
“…7c), thus suggesting a broader range of orientations with AMBER94. Experimentally, LKb7 peptides have been shown to form stable b-sheet structures with the L amino acids adsorbed closer to the surface than the K amino acids on hydrophobic surfaces by DeGrado and Lear [7] (air-water interface and an apolar surface), by Phillips and coworkers [8] (hydrophobic polystyrene), and by Castner and coworkers [9,11] (CH 3 -SAMs). In addition, using infrared spectroscopy, DeGrado and Lear indicated that the b-sheet formed by the LKb7 on an apolar surface occurred in an antiparallel structure, while using sum frequency generation (SFG), Castner and coworkers [11] indicated very distinct separation between the L and K amino acid residues on a CH 3 -SAM surface using a 15 amino acid alternating LK peptide (LKb15) as opposed to LKb7.…”
Section: The Lkb7 Pair Adsorbed To the Ch 3 -Sammentioning
confidence: 99%
See 2 more Smart Citations
“…We have also studied the structure and orientation of LKα14 on PS, silica, self-assembled monolayers (SAMs), and fluorocarbon (FC) surfaces using SFG combined with other spectroscopic methods (9,16,18,(41)(42)(43). These studies show that adsorbed LKα14 has an α-helical secondary structure, and on the hydrophobic surfaces (PS and FC) the leucine side chains were oriented towards, and the lysine side chains oriented away from, the surface.…”
mentioning
confidence: 99%